Optimal use of SGLT2 inhibitors in diabetic kidney transplant recipients - Pham, Phuong-Thu T.; Pham, Phuong-Chi T. (Frontiers in Nephrology, 2022)
Sodium-glucose cotransporter 2 inhibitor (SGLT2i), a glucosuric agent initially approved for use as an antidiabetic agent, was unexpectedly found to confer cardio-and renoprotective effects in individuals with or without type 2 diabetes mellitus. Despite mounting evidence suggesting that SGLT2i provides cardio- and renoprotective benefits in both diabetic and non-diabetic and in chronic kidney disease (CKD) patients in the general population, reservations for its use in the transplant setting persist due to concerns for increased risk of genital mycotic and urinary tract infections. A comprehensive review of the literature on the safety and efficacy of SGLT2i use in diabetic kidney transplant recipients is herein presented followed by authors’ opinion on its optimal use in this patient population.